Digitalization of double entry bookkeeping and marketing of Wonogiri Cashew Farmers Group towards globalization - Heru Suwasono; Bagas Dwi Yulianto; Endang Anggiratih (University of Merdeka Malang, 2025)
This service focuses on digitizing bookkeeping and marketing in the cashew industry. Despite existing for over 20 years and has not developed. The team aims to address this issue by providing bookkeeping training for businesses, making their transactions more visible and allowing for a better understanding of their financial results. Currently, business revenue is often mixed with personal funds, leading to the perception of small profits. The team offers marketing training to help businesses stay up to date with industry trends. These training sessions are conducted to improve the industry's overall knowledge and skills. The outcomes of the service include the creation of a web platform for industry players, a discussion group on WhatsApp, and the introduction of bookkeeping through physical books or Excel. These tools are crucial for expanding product reach and enabling better financial management, helping businesses plan for growth and make informed decisions regarding loans and other financial matters.